Experimental investigation of hybrid photovoltaic solar thermal collector (PV/T)-adsorption desalination system in hot weather conditions. (1st September 2022) - Ghazy, Mohamed; Ibrahim, E.M.M.; Mohamed, A.S.A.; Askalany, Ahmed A.
Abstract: Solar photovoltaic is one of the most famous renewable energy collectors and the most prevalent. The drawback that restricts the widespread use of photovoltaic cells is their relatively low efficiency in hot weather conditions. The current work investigates effect of cooling photovoltaic cells using an adsorption desalination/cooling system (ADS). The proposed system is a new application that simultaneously produces electrical power and desalinated water. Photovoltaic cells are cooled by chilled water produced during the desalination process of the ADS to improve the efficiency of photovoltaic cells and maximize the utilization of the ADS. A sheet and tube thermal collector is fabricated to cool the rear PV panel (PV/T). It is found that the proposed system positively affects the performance of both PV cells and the desalination system. The results showed that the PV/T's electrical and thermal efficiencies are 11.5% and 77.5%, respectively, at 1000 W/m 2 solar radiation and 45 °C ambient temperature. Performance parameters of the ADS are 6.3 (m 3 /ton-day) specific daily water productions, 152.2 W/kg specific cooling power, and 0.25 coefficient of performance. There is an improvement in the electrical power, specific daily water productions, coefficient of performance, and specific cooling power by 17.5%, 19.69%, 9.9%, and 6.13%, respectively. Highlights: Cooling PV by adsorption desalination/cooling system is presented. Performance of PV/T-adsorption desalination is investigated. Electrical power is improved by 17.5%. Specific daily water productions is improved by 19.69.